God Help the Child - Morrison, Toni (London Vintage, 2015)
WHAT YOU DO TO CHILDREN MATTERS. AND THEY MIGHT NEVER FORGET. Sweetness wants to love her child, Bride, but she struggles to do so as a mother should. Bride, now glamorous, grown-up, ebony-black and panther-like, wants to love her man, Booker, but she finds herself betrayed by a moment in her past, a moment born of a desperate burn for the love of her mother. Booker cannot fathom Bride's depths, with his own lovelorn past bending him out of shape. Can they find a way through the damage wrought on their blameless childhood souls, to light and happiness, free from pain?
Keywords: Mothers and daughters -- African Americans